The Green Paradox: Examining the Mediating Role of Dynamic Capabilities in the Relationship between ESG Performance and Long-term Firm Value in Emerging Markets - Ginanjar, Seandy; Setiawan Sariyoga; Andi (PT Inovasi Pratama Internasional, 2026)
This article investigates how dynamic capabilities mediate the relationship between environmental, social, and governance (ESG) performance and long-term firm value in emerging markets, where institutional volatility, regulatory gaps, and resource constraints create unique implementation challenges. Drawing on qualitative evidence from multiple case studies of listed and large private firms in selected Asian and African emerging economies, the study explores how firms translate ESG performance into enduring value through sensing, seizing, and reconfiguring capabilities. Semi-structured interviews with senior managers, sustainability officers, and investors are combined with document analysis of ESG reports, corporate disclosures, and regulatory guidelines to construct a comprehensive narrative of ESG–capability–value linkages. The findings indicate that ESG performance alone does not guarantee long-term value; instead, value creation depends on firms’ ability to develop absorptive, adaptive, and integrative dynamic capabilities that align ESG initiatives with core strategy, innovation, and stakeholder expectations. The study further uncovers a